Beyond Widespread Mecp2 Deletions to Model Rett Syndrome: Conditional Spatio-Temporal Knockout, Single-Point Mutations and Transgenic Rescue Mice - Li, Wei (2012)
Rett syndrome (RTT) is one of the leading causes of intellectual disabilities in women. In addition to a few autistic features, characteristic symptoms that distinguish from classical autism include stereotypic hand movements, motor coordination deficits, breathing abnormalities, seizures and loss of acquired speech as well as purposeful hand use. RTT is highly associated with MECP2, the gene encoding for the transcription factor that binds methylated Cytosine in C-p-G islands in DNA, controlling gene expression and chromatin remodeling. In this review, we will briefly discuss current perspectives on MeCP2 function, and then will describe in detail novel mouse models of RTT based on loss-of-function of Mecp2 and their use for establishing rescue models, wherein we pay close attention to behavioral and morphological phenotypes.